Advances in multi-photon processes and spectroscopy - Lin, S. H.; Villaeys, A. A.; Fujimura, Y. (World Scientific, 2014)
his volume presents state-of-the-art research in multiphoton processes and spectroscopy, focusing on theoretical developments, experimental advances, and applications in atomic and molecular physics.